Design of optical system for binocular fundus camera. (31st October 2017) - Wu, Jun; Lou, Shiliang; Xiao, Zhitao; Geng, Lei; Zhang, Fang; Wang, Wen; Liu, Mengjia
Abstract: A non-mydriasis optical system for binocular fundus camera has been designed in this paper. It can capture two images of the same fundus retinal region from different angles at the same time, and can be used to achieve three-dimensional reconstruction of fundus. It is composed of imaging system and illumination system. In imaging system, Gullstrand Le Grand eye model is used to simulate normal human eye, and Schematic eye model is used to test the influence of ametropia in human eye on imaging quality. Annular aperture and black dot board are added into illumination system, so that the illumination system can eliminate stray light produced by corneal-reflected light and omentoscopic lens. Simulation results show that MTF of each visual field at the cut-off frequency of 90lp/mm is greater than 0.2, system distortion value is −2.7%, field curvature is less than 0.1 mm, radius of Airy disc is 3.25um. This system has a strong ability of chromatic aberration correction and focusing, and can image clearly for human fundus in which the range of diopters is from −10 D to +6 D(1 D = 1 m −1 ).